Common iliac artery aneurysm as a cause of massive hematuria post TURBT. Case report. (2020) - Alkhatatbeh, Hassan; Alzaghari, Dima; Alharahsheh, Sufian; Azab, Mohammed; Almalkawi, Adeeb; Alnsour, Rami; ALsamen, Abd AL-Hakeem Abu
Highlights: Bleeding after transurethral resection of bladder tumor is usually minimal and resolve spontaneously within days or weeks. Common iliac artery aneurysm is a rare but can cause severe hematuria after cystoscopy with minimal manipulation. Endovascular graft repair is minimally invasive procedure that showed excellent results in treatment of common iliac artery aneurysm. Abstract: Introduction: Transurethral resection of bladder tumor (TURBT) is an outpatient simple procedure that aims to remove bladder masses. Bleeding post TURBT is usually minimal and resolve completely within days or weeks. Massive bleeding after TURBT for small bladder masses is unusual. In this article we will report a case of unexpected massive hematuria that occurred after simple TURBT. Presentation of case: A 69 patient who presented to our clinic complaining of intermittent painless gross hematuria. Ultrasound showed 1 cm bladder mass for which TURBT was done. On the 3rd post operative day the patient presented to ER complaining of massive hematuria and drop in hemoglobin. CT scan showed large left common iliac artery aneurysm which was managed using Endovascular graft repair (EVAR). Discussion: Common iliac artery aneurysm is rare entity. Usually it is asymptomatic. However if it is large it can compress the perivesical vessels causing engorgement of these vessels that can manifest as massive hematuria after minimal endoscopic manipulation of the bladder. Conclusion: Massive hematuria after simple TURBT is unusual for urologists. If it happens it may indicates iliac aneurysm or vascular malformation.